1998
DOI: 10.1139/f98-135
|View full text |Cite
|
Sign up to set email alerts
|

Regimes and stock-recruitment relationships in Japanese sardine (Sardinops melanostictus), 1951-1995

Abstract: We used reproductive success, rather than abundance or catch, to identify regimes because reproductive success responds faster to environmental changes. Peak abundance of Japanese sardine during 1951-1995 was about 1000 times higher than minimum abundance. A regime shift occurred in the early 1970s when carrying capacity (measured using spawner-recruit models) increased by about 75 times. We hypothesize that this was due to large-scale changes in the Kuroshio and Oyashio Current systems. Long-term environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 7 publications
5
83
1
1
Order By: Relevance
“…recruitment may be defined as the relation between the size of the spawning stock and the subsequent yearly class derived from this spawning (ricker, 1954, 1975Hilborn and Walters, 1992). the literature provides examples in which the relationship between diverse environmental factors and recruitment for different species of sardine is evident (Wada and Jacobson, 1998;Cole, 1999;guisande et al, 2001;Yatsu et al, 2005), and in which recruitment appears to oscillate, depending on the prevailing climatic conditions. For the Pacific sardine off the west coast of the Baja California peninsula, the few studies that have been performed on stock recruitment (Morales-Bojórquez, 1999, 2002Morales-Bojórquez et al, 2003) have shown that it is susceptible to the surface temperature of the sea in this zone.…”
Section: Decision Analysis With Bayesian Criterionmentioning
confidence: 99%
“…recruitment may be defined as the relation between the size of the spawning stock and the subsequent yearly class derived from this spawning (ricker, 1954, 1975Hilborn and Walters, 1992). the literature provides examples in which the relationship between diverse environmental factors and recruitment for different species of sardine is evident (Wada and Jacobson, 1998;Cole, 1999;guisande et al, 2001;Yatsu et al, 2005), and in which recruitment appears to oscillate, depending on the prevailing climatic conditions. For the Pacific sardine off the west coast of the Baja California peninsula, the few studies that have been performed on stock recruitment (Morales-Bojórquez, 1999, 2002Morales-Bojórquez et al, 2003) have shown that it is susceptible to the surface temperature of the sea in this zone.…”
Section: Decision Analysis With Bayesian Criterionmentioning
confidence: 99%
“…En otras latitudes también existen evidencias de la existencia de regímenes ambientales Mantua, 1999aMantua, , 1999bHare & Mantua 2000, 2001Hollowed, 2001) y su efecto en los diferentes recursos pesqueros; tal es el caso de su influencia en la dinámica poblacional del lenguado del Pacífico norte ("halibut"), del "pollock" de Alaska o sardina del Pacífico norte (Theragra chalcogramma), la sardina japonesa (Sardinops melanostictus) y el lenguado de roca del Mar de Bering (Lepidopsetta bilineata), entre los más importantes, afectando los reclutamientos, procesos de denso-dependencia y patrones de crecimiento individual y poblacional (Jacobson & MacCall, 1995;Quinn & Niebauer, 1995;Hare, 1996;Francis et al, 1998;Wada & Jacobson, 1998;Walters & Wilderbuer, 2000;Clark & Hare, 2002).…”
Section: Discussionunclassified
“…1 Annual total population abundance (all ages, available after 1977, gray and unfilled bars) and recruitment (age 0, gray bars) of Japanese sardine in Pacific waters (after Wada and Jacobson [6], Nishida et al [7]), and catch in the Pacific off the Sanriku and the eastern Hokkaido areas of northern Japan (closed diamonds and solid line)…”
Section: Methodsmentioning
confidence: 99%
“…For the total population abundance (standing stock of all ages) and the recruitment of each year class (cohort abundance at age 0), we referred to the estimates gained from the virtual population analysis performed in Wada and Jacobson [6] and Nishida et al [7]. We examined variations in both the L t at each age and the CF for different BLs with respect to population abundance and year-class recruitment among the 1975-2002 year classes.…”
Section: Methodsmentioning
confidence: 99%